2022
DOI: 10.3390/ijms23147578
|View full text |Cite
|
Sign up to set email alerts
|

A Focal Impact Model of Traumatic Brain Injury in Xenopus Tadpoles Reveals Behavioral Alterations, Neuroinflammation, and an Astroglial Response

Abstract: Traumatic Brain Injury (TBI) is a global driver of disability, and we currently lack effective therapies to promote neural repair and recovery. TBI is characterized by an initial insult, followed by a secondary injury cascade, including inflammation, excitotoxicity, and glial cellular response. This cascade incorporates molecular mechanisms that represent potential targets of therapeutic intervention. In this study, we investigate the response to focal impact injury to the optic tectum of Xenopus laevis tadpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 76 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…In conclusion, our results allow us to believe that our technique may represent a promising and dependable means of conducting a post-mortem diagnosis of TBI [42]. Moreover, the study shows the important role of FOXO3a in neuronal autophagy and apoptosis regulation and suggests FOXO3a as a possible potential pharmacological target to prevent the onset of secondary injuries and to improve the outcome of patients who have suffered from TBI, in terms of reducing neurological deficits [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 54%
“…In conclusion, our results allow us to believe that our technique may represent a promising and dependable means of conducting a post-mortem diagnosis of TBI [42]. Moreover, the study shows the important role of FOXO3a in neuronal autophagy and apoptosis regulation and suggests FOXO3a as a possible potential pharmacological target to prevent the onset of secondary injuries and to improve the outcome of patients who have suffered from TBI, in terms of reducing neurological deficits [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 54%
“…NaF dye has been previously shown to be prevented from exciting the brain at stage 55 in uninjured tadpoles, indicating an intact BBB (D e jesus andino et al 2016). Adapting the method used in a recent study using X. laevis tadpoles to model traumatic brain injury (S pruiell eldridge et al 2022) for our younger tadpoles, we injected 9.2 nl of 0.1 mg/ml sodium fluorescein (NaF) into the 4th ventricle (Figure 4A) at stage 47. BBB permability was then measured by tracking dye distribution over 30 minutes (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted June 2, 2024. ; https://doi.org/10.1101/2024.05. 29.596533 doi: bioRxiv preprint 4 Recent advances in flexible electronics [17][18][19][20][21] have yielded "tissue-like" mesh microelectronics: submicrometer-thick mesh electronics with tissue-level flexibility. Mesh microelectronics mimic the physicochemical properties of the extracellular matrix and are thus capable of seamlessly integrating into in vitro and in vivo neural tissues, forming gliosis-free bioelectronic interfaces and enabling long-term, stable, multichannel electrical recordings in 3D brain tissues at single-unit, single-spike spatiotemporal resolution over months 22 .…”
Section: Main Textmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted June 2, 2024. ; https://doi.org/10.1101/2024.05. 29.596533 doi: bioRxiv preprint revealed that the presence of microelectronics had no discernible impact on embryo development or subsequent behaviors. Our device enables tissue-wide, continuous recording of neuron electrical activity at millisecond temporal resolution.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation